2017
DOI: 10.7575/aiac.ijalel.v.7n.1p.64
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Critical Thinking as the Predictors of Autonomous Language Learning in EFL Contexts

Abstract: The thrust of the present study was to systematically investigate the relationship between EFL learners' Self-Efficacy (SE), Critical Thinking (CT), and their Autonomy (AU). To this end, 196 male and female EFL learners, within the age range of 20 to 30 (Mage= 25) were selected based on convenience sampling strategy. They were asked to fill in three questionnaires, namely Sherer, Maddux, Mercadante, Prentice-Dunn, Jacobs, and Rogers' SE Scale (1982), Honey's CT questionnaire (2000), and Zhang and Li's Learner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There is adequate evidence that a high-level self-perceived efficacy is typically associated with successful action and good performance while a doubt usually leads to failure or inaction. Individuals with high SE are also considered more likely to be equipped with CTD, which indicates a positive association between the two dimensions [3,8]. Pervious research suggests that SE plays a potent role in human agency, which has been showed to be a powerful determinant and mediator of academic outcomes and motivational effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is adequate evidence that a high-level self-perceived efficacy is typically associated with successful action and good performance while a doubt usually leads to failure or inaction. Individuals with high SE are also considered more likely to be equipped with CTD, which indicates a positive association between the two dimensions [3,8]. Pervious research suggests that SE plays a potent role in human agency, which has been showed to be a powerful determinant and mediator of academic outcomes and motivational effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…The literature in this area identifies self-efficacy or academic self-efficacy as one of the variables underlying learner autonomy (Flannagan, 2007;Macaskill & Denovan, 2013;Mahmoudi & Asadi, 2016;Nosratinia & Hossaini, 2018;Overall, Deane, & Peterson, 2011;Ponton, Derrick, Confessore, & Rhea, 2005;Pu, 2009;Tılfarlıoğlu & Çiftçi, 2011). Bandura (1997) defined self-efficacy as one's belief in one's ability to succeed in specific situations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not abnormal to presume that the self-efficacy beliefs of individuals may be associated with their autonomous learning behaviours since self-efficacy beliefs underlie what they think, how they feel, how they make their choices and how they motivate themselves (Bandura, 1997). Furthermore, various studies have confirmed this relationship (Flannagan, 2007;Macaskill & Denovan, 2013;Mahmoudi & Asadi, 2016;Nosratinia & Hossaini, 2018;Overall et al, 2011;Ponton et al, 2005;Pu, 2009;Tılfarlıoğlu & Çiftçi, 2011). The statistical or theoretical results of these studies showed a strong relationship between learner autonomy and selfefficacy.…”
Section: Introductionmentioning
confidence: 99%